Frailty screening in older adults: is annual screening necessary in primary care?. (8th July 2021) - Lee, Linda; Jones, Aaron; Hillier, Loretta M; Costa, Andrew; Patel, Tejal; Parikh, Ruchi
Abstract: Background: The Case-finding for Complex Chronic Conditions in Adults 75+ (C5-75) involves annual frailty screening in primary care using dual-trait screening measures of handgrip strength and gait speed, with additional screening for co-existing conditions in those deemed frail. Objective: To identify low-risk individuals who could be screened for frailty every 2 years, rather than annually. Methods: This study examined a prospective cohort of patients who completed at least two annual C5-75 screenings between April 2014 and December 2018. Handgrip strength and gait speed on initial assessment were categorized based on proximity to frailty thresholds and were used to predict frailty risk on the second assessment. We used Fisher's exact test to assess differences in risk. Logistic regression models tested associations between independent variables of age, patient activity level, falls history, grip strength and gait speed on first assessment and dependent variable of frailty on subsequent assessment. Results: Analyses included 571 patients with two annual assessments. Frailty risk on the second assessment was significantly higher for patients who had gait speed or grip strength within 20% of the frailty threshold (5.7%), compared with the other categories (0.7%, 0.9%, 0%; P = 0.002); 60% of patients fell within these lower risk categories. Controlling for grip strength and gait speed, no other measures had significant associations with frailty risk. Conclusions: Our results demonstrate that 60% patients are at low risk (<1%) of transitioning to frailty by the next annual assessment. Reducing screening frequency from annually to every 2 years may be appropriate for these patients. Lay Summary: Frail older adults are at greater risk for illness, functional decline, increased health service use and institutionalization. Adults 75 years of age and older should be screened regularly for frailty to provide early treatment for co-occurring conditions that may impact frailty but that may also be affected by frailty. Walking (gait) speed and handgrip strength are feasible measures of frailty to use on an annual basis in primary care. This study assesses the transition to frailty over a 1-year time period for the purpose of streamlining frailty screening in primary care for those patients who do not require annual screening. We found that when patients' grip strength and gait speed scores were 20% higher than the point at which people are identified as frail, they are at low risk for becoming frail by their next annual assessment. Frailty screening every 2 years may be appropriate for these patients. This streamlined screening process may make it more feasible for busy family practices to implement this type of frailty screening.